Predisposition towards hallucinatory experiences in Peru: examining the continuity-pathology in normal individuals clinical and nonclinical - Parra, Alejandro (2009)
The purpose of the present study is to test whether hallucinatory experiences respond to the dimensionality principle and to detect potential differences between a group of “hallucinators” and a group of “non-hallucinators” with regard to personality traits in 214 Peruvian undergraduates students (non-clinical sample) and 30 outpatients (clinical sample). Among a sample of undergraduates, it was predicted that those who reported a number of anomalous perceptual experiences would score higher than nonexperiencers on the hallucination prone (auditive, visual, hipnagogic/hipnopompic and tactile), fantasy proneness, absorption, dissociation, and the cognitive-perceptual factor of the schizotypal questionnaire. All the predictions were significantly confirmed except those concerning interpersonal and disorganized schizotypy.